A new Leptographium species from the roots of declining Pinus sylvestris in Switzerland. Issue 4 (31st March 2017) - Marincowitz, S.; Duong, T. A.; Heiniger, U.; Wingfield, B. D.; Wingfield, M. J.; de Beer, Z. W.
Summary: Scots pine ( Pinus sylvestris ) trees have been declining in the Rhône valley, Switzerland, for almost three decades. In an assessment of the role of fungi in this syndrome, the dominant fungus isolated from stained roots was a Leptographium species, morphologically similar to the asexual state of Grosmannia serpens . We examined isolates of this fungus based on DNA sequences of four protein‐coding genes including actin, β‐tubulin, calmodulin and translation elongation factor‐1 alpha. The results showed that they were of a distinct, undescribed taxon related to species in the Grosmannia serpens and G. wageneri complexes. The fungus, described here as Leptographium rhodanense sp. nov., resembles other species in the two species complexes morphologically, and most probably ecologically, as is suggested by the fact that it was isolated from stained pine roots.